(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The nature and genesis of imagination has been a subject of serious concern with the philosophers, poets and literary scholars since the advent of poetics and still continues. But for T.E. Hulme, Ezra Pound, T.S. Eliot and their few followers almost all of the modern literary scholars acknowledge imagination as the faculty essential to creativity. In Romanticism, imagination is the distinctive element which contributes to romantic vision.